Developing An al-Nahw al-Wadhih Book With A Handout In school (Research and Development Study At Tgk. Chiek Oemar Diyan Aceh Besar): (Tgk. Chiek Oemar Diyan Aceh Besar دراسة البحث والتطوير بمعهد ) في المدرسة الثانوية Handout تطوير كتاب النحو الواضح بــ - Zulfiani, Lia; Syarifuddin, Syarifuddin (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2024)
In this study, the researcher observed that teachers in Oemar Diyan Boarding only use textbooks in teaching and learning activities, causing a decrease in the quality of learning and leading to a decrease in the quality of education. Therefore, students find it difficult to learn Arabic and eventually find the lesson as a burden. As for efforts to overcome these problems, researchers used the Handout media to facilitate students in understanding the lessons, especially in the mabni and mugrab subjects. The purposes of this research were to find out the product development of an-Nahwu al-Wadhih book in mabni and mugrab chapter with media Handout for second-grade students of junior high school, to investigate the students’ responses to an-Nahwu al-Wadhih on Dhamir chapter with media handout, and to explore the validity level of anNahwu al-Wadhih on Dhamir chapter with handout media according to expert validations. Research and development (R&D) methods were utilized in collecting data. Furthermore, the population of this research was 162 students, however, to meet the objective of this research 28 students were chosen as samples. This research produced a new product that is a book titled “Attaisir Fi Ta'lim mabni and mugrab” After going through expert validation processes. The students’ responses to this new product showed that they agreed to the development of the an-Nahwu alWadhih book in the Dhamir chapter with a media mind mapping making it easier for them to learn. The result is obtained from T-test Sig (.05<.100). This shows that the hypothesis is zero (ho) is rejected and hypothesis (Ha) is accepted, it is evident that the usage of handouts is influential in improving student’s understanding of mabni and mugrab lesson.